Induction of Promyelocytic Leukemia (PML) Oncogenic Domains (PODs) by Papillomavirus - Nakahara, Tomomi (2007)
Promyelocytic leukemia oncogenic domains (PODs), also called nuclear domain 10 (ND10), are subnuclear structures that have been implicated in a variety of cellular processes as well as the life cycle of DNA viruses including papillomaviruses. In order to investigate the interplay between papillomaviruses and PODs, we analyzed the status of PODs in organotypic raft cultures of human keratinocytes harboring HPV genome that support the differentiation-dependent HPV life cycle. The number of PODs per nucleus was increased in the presence of HPV genomes selectively within the poorly differentiated layers, but was absent in the terminally differentiated layers of the stratified epithelium. This increase in PODs was correlated with an increase in abundance of post-translationally modified PML protein. Neither the E2 dependent transcription nor viral DNA replication was reliant upon the presence of PML. Implications of these findings in terms of HPV's interaction with its host are discussed.